Investigação do comportamento de placas de base de pilares em aço submetidos a carregamento biaxial - Gasparetto, Angelica (2021)
The connection between the steel column and concrete foundation is made by a steel plate, called base plate, welded to the steel column and connected to the foundation by means of anchor bolts. These connections are used in buildings to transfer loads from structure to foundations, however, Brazilian standard NBR8800: 2008 - Design and execution of steel structures and mixed steel and concrete structures in buildings does not address the design aspects of the connections of these elements. The most diverse literatures provide information about base plate checks submitted in one direction, usually in the most inertial metal profile (column), as is traditionally used. However, studies of biaxial bias directions in the direction of smallest and largest inertia of the steel column make the analysis of the baseplates closer to the real situations. Thus, the present dissertation aims identify the behavior of the base plate connections of columns formed by profile submitted to oblique composite flexural compression. Sixteen models were analyzed, with two international standards (AISC and Eurocode) with three different types of force: biaxial, uniaxial in the axis of lesser inertia and uniaxial in the axis of greater inertia, through the Components Method Based on Finite Element - CBFEM. A statistical approach was also performed, analyzing the correlation of variables and analysis of variance. As conclusions, it is possible to say that it is necessary to carry out the verification of base plates submitted to biaxial flexion, as the difference in tension obtained in the biaxial analysis, when compared to the uniaxial in the axis of greatest inertia, was significant.